Chemical structure, surface properties and biological activities of the biosurfactant produced by Pseudomonas aeruginosa LBI from soapstock - Benincasa, M.; Abalos, A.; Oliveira, I; Manresa, A. (Kluwer Academic Publ, 2004)
Pseudomonas aeruginosa LBI isolated from petroleum-contaminated soil produced rhamnolipids (RLLBI) when cultivated on soapstock as the sole carbon source. HPLC-MS analysis of the purified culture supernatant identified 6 RL homologues (%): R-2 C-10 C-10 28.9; R-2 C-10 C-12:1 23.0; R-1 C-10 C-10 23.4; R-2 C-10 C-12 11.3; R-2 C-10 C-12 7.9; R-2 C-10 C-12 C-12 5.5. To assess the potential antimicrobial activity of the new rhamnolipid product, RLLBI, its physicochemical properties were studied. RLLBI had a surface tension of 24 mN m(-1) and an interfacial tension 1.31 mN m(-1); the cmc was 120 mg l(-1). RLLBI produced stable emulsions with hydrocarbons and vegetable oils. This product showed good antimicrobial behaviour against bacteria: MIC for Bacillus subtilis, Staphylococcus aureus and Proteus vulgaris was 8 mg l(-1), for Streptococcus faecalis 4 mg l(-1), and for Pseudomonas aeruginosa 32 mg l(-1). RLLBI was active against phytopathogenic fungal species, MIC values of 32 mg l(-1) being found against Penicillium, Alternaria, Gliocadium virens and Chaetonium globosum. Due to its physicochemical properties and antimicrobial behaviour, RLLBI could be used in bioremediation treatment and in the food, cosmetic and pharmaceutical industries.
Keywords: antimicrobial agent; biosurfactant; HPLC-MS; liquid chromatography; mass spectrometry; physicochemical properties; Pseudomonas aeruginosa; rhamnolipids